2022
DOI: 10.1111/ajo.13588
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum anaemia in three New Zealand district health board regions: An observational study of incidence and management

Abstract: Background The incidence of postpartum anaemia (PPA) in New Zealand, and the extent of intravenous iron (IV‐iron) use in its treatment, are unknown. Aims To report the incidence of PPA in three district health board (DHB) regions and describe current management of moderate to severe PPA, including by ethnicity. Materials and Methods Retrospective observational study of PPA (haemoglobin (Hb) <100 g/L) in three DHBs from July–December 2019. Cases with moderate to severe PPA (Hb <90 g/L) were reviewed and managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…5 We previously reported that of the 46% of women tested, 38% had PPA (Hb <100 g/L). 5 Pre-birth anemia and postpartum hemorrhage are the most significant contributors to PPA. [6][7][8][9][10][11] PPA is strongly associated with maternal mortality and severe morbidity, including admission to intensive care, particularly after major postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…5 We previously reported that of the 46% of women tested, 38% had PPA (Hb <100 g/L). 5 Pre-birth anemia and postpartum hemorrhage are the most significant contributors to PPA. [6][7][8][9][10][11] PPA is strongly associated with maternal mortality and severe morbidity, including admission to intensive care, particularly after major postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 90%
“…RBC-T is a limited resource and is associated with transfusion reactions including alloimmunization, with serious implications for subsequent pregnancies. 27 In the last decade, third-generation high-single-dose IV-iron formulations have been increasingly used 28,29 as an alternative to, or alongside, RBC-T for the treatment of more severe PPA, 5 and associated with escalating healthcare costs. 30 Despite the increasing popularity of IV-iron, and Patient Blood Management recommendations supporting its use as an alternative to RBC-T for hemodynamically stable women with PPA, 27,31,32 there is a lack of evidence on the comparative safety and effectiveness of IV-iron and/or RBC-T for both woman-centered and laboratorybased outcomes (Caljé et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those tested, and after adjusting for deprivation and region, European women had lower adjusted odds ratios compared to Māori for being identified as having postpartum anaemia in a three-region observational study by Calje et al 4 Cowan et al 5 evaluated the effect of the introduction of the Perinatal Institute's Growth Assessment Protocol (GAP) in the Counties Manukau Health region, South Auckland, New Zealand, on antenatal detection of small-for-gestational-age (SGA) infants and maternal and perinatal outcomes. They found GAP was associated with increased detection of SGA.…”
Section: Māori Women's Reproductive Healthmentioning
confidence: 96%
“…Of those tested, and after adjusting for deprivation and region, European women had lower adjusted odds ratios compared to Māori for being identified as having postpartum anaemia in a three‐region observational study by Calje et al 4 …”
mentioning
confidence: 97%